1997
DOI: 10.1023/a:1018889120034
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Saliva contains several factors that protect the alimentary canal mucosa against acidity. We measured the secretory carbonic anhydrase (CA VI) levels in the saliva of patients with gastrointestinal disorders using a time-resolved immunofluorometric assay. The mean enzyme concentrations were found to be lower in patients with verified esophagitis, gastric ulcer, or duodenal ulcer than in control patients with nonacid peptic diseases. The biochemical data from the enzyme activity assays and western blots of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…The affinity for BCA II of the benzenesulfonamide with four Gly residues (71, K d ≈ 210 nM) was ~3-fold lower than those for 69 and 70. The affinities of benzyl-ether-terminated benzenesulfonamides with tails of oligoethylene glycol (77)(78)(79)(80)(81)(82) for BCA II decreased monotonically with increasing tail length, but only by a factor of 2 over the range of one (77) to six (82) residues. These affinities were only 4-5-fold higher than for methyl-ether-terminated benzenesulfonamides with oligoethylene glycol tails (72)(73)(74)(75)(76).…”
Section: Influence Of Fluorination On the Secondary Recognition Elementmentioning
confidence: 99%
“…The affinity for BCA II of the benzenesulfonamide with four Gly residues (71, K d ≈ 210 nM) was ~3-fold lower than those for 69 and 70. The affinities of benzyl-ether-terminated benzenesulfonamides with tails of oligoethylene glycol (77)(78)(79)(80)(81)(82) for BCA II decreased monotonically with increasing tail length, but only by a factor of 2 over the range of one (77) to six (82) residues. These affinities were only 4-5-fold higher than for methyl-ether-terminated benzenesulfonamides with oligoethylene glycol tails (72)(73)(74)(75)(76).…”
Section: Influence Of Fluorination On the Secondary Recognition Elementmentioning
confidence: 99%
“…For example, CA VI displaces 125 I-NGF bound to enriched taste bud membrane fractions (24). Although the exact physiological significance of milk CA VI remains undefined here, we suggest that, as an acid-resistant enzyme (11), it may function as a trophic growth factor in the infant alimentary tract, which undergoes pronounced growth and functional maturation during the immediate postnatal period.…”
Section: Discussionmentioning
confidence: 87%
“…Recent studies have, in turn, provided new information about the function of the secretory CA VI. It has been proposed that this isoenzyme may participate in protecting the teeth from caries (10) and in neutralizing excess acid in the mucous layer covering the esophageal and gastric epithelium (11). Another novel role for CA VI became apparent when Thatcher et al (12) identified gustin, a salivary factor implicated in taste bud growth, as CA VI.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CA-VI has been purified from saliva or parotid glands of humans [10], rats [3] and cattle [1,5]. It may participate in the regulation of salivary pH and buffer capacity and protect the upper alimentary canal against excess acidity [13]. Kivela et al reported that salivary CA-VI is not directly involved in the regulation of pH in saliva [8].…”
mentioning
confidence: 99%